Genome-Wide Identification and Characterization of Long Noncoding RNAs in Populus × canescens Roots Treated With Different Nitrogen Fertilizers - Zhou, Jing; Yang, Ling-Yu; Chen, Xin; Shi, Weng-Guang; Deng, Shu-Rong; Luo, Zhi-Bin (Frontiers in Plant Science, 2022)
Nitrate (NO3-) and ammonium (NH4+) are the primary forms of inorganic nitrogen acquired by plant roots. LncRNAs, as key regulators of gene expression, are a class of noncoding RNAs larger than 200 bp. However, knowledge about the regulatory role of lncRNAs response to different nitrogen forms remains limited, particularly in woody plants. Here, we performed strand-specific RNA sequencing of P. × canescens roots treated with three different nitrogen fertilization treatments. In total, 324 lncRNAs and 6112 mRNAs were identified as showing significantly differential expression between the NO3- and NH4NO3 treatments. Moreover, 333 lncRNAs and 6007 mRNAs showed significant differential expression patterns between the NH4+ and NH4NO3 treatments. Further analysis suggested that these lncRNAs and mRNAs have different response mechanisms for different nitrogen forms. In addition, functional annotation of cis and trans target mRNAs of differentially expressed lncRNAs indicated that 60 lncRNAs corresponding to 49 differentially expressed cis and trans target mRNAs were involved in plant nitrogen metabolism and amino acid biosynthesis and metabolism. Furthermore, 42 lncRNAs were identified as putative precursors of 63 miRNAs, and 28 differentially expressed lncRNAs were potential endogenous target mimics targeted by 96 miRNAs. Moreover, ceRNA regulation networks were constructed. MSTRG.6097.1, MSTRG.13550.1, MSTRG.2693.1 and MSTRG.12899.1, as hub lncRNAs in the ceRNA networks, are potential candidate lncRNAs for studying the regulatory mechanism in poplar roots under treatment with different nitrogen fertilization treatments. The results provide a basis for obtaining insight into the molecular mechanisms of lncRNA responses to different nitrogen forms in woody plants.